Literasi dan Pemanfaatan Media Sosial pada Masyarakat Pesisir Desa Seraya, Karangasem, Bali - Samuel Raskita Sitepu; Ida Bagus Gde Pujaastawa; Ida Bagus Oka Wedasantara (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
Appropriate utilization of social media can bring positive value to human life. Awareness of this makes social media used by all groups regardless of age, economic status, and location. As seen in coastal communities in Seraya Village who are familiar with the use of social media ranging from children to adults with their respective functions and purposes. Another interesting point relates to the views of some research results that mention fishermen and coastal communities as poor communities, which contrasts with this research. This research aims to find out the process of digital literacy and the use of social media in coastal communities. The method used is qualitative in the form of ethnography of coastal communities with data collection techniques through interviews, participant observation, and literature study.